Psychosocial adjustment to a prostate cancer diagnosis in a cohort of radical prostatectomy patients in Quebec, Canada. Issue 4 (27th February 2019) - Wissing, Michel D.; Chevalier, Simone; O'Flaherty, Ana; McKercher, Ginette; Aprikian, Saro; Saad, Fred; Carmel, Michel; Lacombe, Louis; Hamel, Marc; Aprikian, Armen
Abstract: Objective: The psychosocial impact of a prostate cancer diagnosis significantly affects a patient's quality of life. We studied patient communication at the time of diagnosis and its impact on psychosocial adjustment of patients. Methods: This is a cross‐sectional data analysis from self‐administered questionnaires in the PROCURE biobank study, consisting of a cohort of patients with localized prostate cancer undergoing radical prostatectomy in Québec (Canada), 2006 to 2013. Odds ratios (OR) and their respective 95% confidence intervals (95% CI) were calculated using binary or ordered logistic regression models. Results: Data from 1841 patients were analyzed. The median age of patients was 62 years (range 41‐80 years), the majority was French‐Canadian (68.3%) and married (79.6%). Most patients (90.1%) considered conversations with their treating physician a useful information source. Patients were dissatisfied on the communication when receiving their diagnosis by telephone (OR = 0.19, 95% CI, 0.11‐0.33). Younger patients were also more dissatisfied. Most patients preferred to receive information on prostate cancer (89.5%) and radical prostatectomy (88.0%) at the time of diagnosis, while only 58.8% and 52.4% of patients received this information at this stage. Patients who were dissatisfied with the communication of the diagnosis had more negative responses, such as increased worries and fear ( P  < 0.05). The five most useful coping mechanisms were physical activity (62.3%), breathing exercises (44.5%), music (32.8%), faith (30.3%), and muscle relaxation (30.1%), but varied by demographics. Conclusions: This study highlights the importance of physicians communicating a prostate cancer diagnosis well to their patients. Patients may benefit from individually tailored interventions to facilitate their overall coping.